In vitro antiproliferative activity, docking study, and plausible mode of action of (+)-2,2′-epicytoskyrin A against breast cancer MCF-7 and T47D cell lines - Agus Budiawan Naro Putra; Kartika Dyah Palupi; Ahmad Fathoni; Listiana Oktavia; Endah Puji Septisetyani; Arif Nurkanto; Praptiwi Praptiwi; Dewi Wulansari; Adi Santoso; Dwinna Rahmi; Andria Agusta (Beni-Suef University Journal of Basic and Applied Sciences)
Abstract Background The endophytic fungus Diaporthe sp. GNBP-10 has been reported to produce metabolite bis-anthraquinone (+)-2,2′-epicytoskyrin A in high titers. In this study, we evaluated the potential of this metabolite as an anti-breast cancer agent by conducting antiproliferative activity studies against two breast cancer cell lines, MCF-7 and T47D. Materials and methods The antiproliferative activity of (+)-2,2′-epicytoskyrin A was determined by a 3-[4,5-dimethylthiazol-2-yl]-2,5 diphenyl tetrazolium bromide (MTT) assay, fluorescence microscopy, and flow cytometry. In addition, the mode of action was assessed by several techniques, including the formation of apoptotic bodies using scanning electron microscopy (SEM) and the interaction or intercalation between (+)-2,2′-epicytoskyrin A with calf thymus DNA as indicated by the UV and 1H-NMR spectra. Moreover, molecular docking was also conducted. Results (+)-2,2′-Epicytoskyrin A exhibited significant antiproliferative effects against MCF-7 and T47D cells. The half-maximal inhibitory concentration (IC50) values for MCF-7 and T47D cells were 50.77 ± 33.23 µM and 36.24 ± 12.57 µM, respectively. (+)-2,2′-Epicytoskyrin A induced cancer cell death and promoted the formation of apoptotic bodies in both cell lines. These phenomena were expected to be facilitated by the DNA-binding ability of hydrogen atoms contained in (+)-2,2′-epicytoskyrin A. Molecular docking data indicated that (+)-2,2′-epicytoskyrin A might bind to the minor groove area of DNA, suggesting its potential as a DNA intercalator. Conclusion This study highlighted the potential of (+)-2,2′-epicytoskyrin A as a promising candidate for future breast cancer treatment. Graphical abstract